2016
DOI: 10.4103/0975-7406.171697
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antioxidant activity of Manihot esculenta Crantz in wistar rats

Abstract: Aims:The study aimed to explore the antioxidant activity of ethanolic leaf extract of Manihot esculenta Crantz leaves (MEC) in wistar rats.Materials and Methods:Ethanolic extract of MEC leaves in the doses of 50 mg/kg, 100 mg/kg, and 200 mg/kg were used in wistar rats of either sex. The oxidative stress was produced by overdose of acetaminophen and estimation of serum concentration of various enzymes such as malonaldehyde (MDA), superoxide dismutase (SOD), reduced glutathione (GSH), and catalase (CAT) were mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 16 publications
(19 reference statements)
1
8
0
Order By: Relevance
“…Inhibition of the mitochondrial membrane pore opening by the ethanolic extract of Manihot esculentaleaf was observed at intermediate concentrations in high-fat-diet-fed rat liver, at the lower concentrations in uni-nephrectomized, high-fat-diet-fed rats, and at all the extract concentrations in the high-fat-diet-fed, uni-nephrectomized rats. These findings were consistent with the results of another study which revealed that the crude ethanolic extract of Manihot esculenta leaf inhibited mitochondrial pore opening in both normal and type 2 diabetic Sprague-Dawley rats, both in vivo and in vitro, which may be due to the significant antioxidant properties of the extract [47,60]. These observations suggest that the protective role of Manihot esculenta leaf extract can be harnessed both when insulin-resistance develops following kidney donation or damage, and when there has been insulin resistance before nephrectomy.…”
Section: Resultssupporting
confidence: 92%
“…Inhibition of the mitochondrial membrane pore opening by the ethanolic extract of Manihot esculentaleaf was observed at intermediate concentrations in high-fat-diet-fed rat liver, at the lower concentrations in uni-nephrectomized, high-fat-diet-fed rats, and at all the extract concentrations in the high-fat-diet-fed, uni-nephrectomized rats. These findings were consistent with the results of another study which revealed that the crude ethanolic extract of Manihot esculenta leaf inhibited mitochondrial pore opening in both normal and type 2 diabetic Sprague-Dawley rats, both in vivo and in vitro, which may be due to the significant antioxidant properties of the extract [47,60]. These observations suggest that the protective role of Manihot esculenta leaf extract can be harnessed both when insulin-resistance develops following kidney donation or damage, and when there has been insulin resistance before nephrectomy.…”
Section: Resultssupporting
confidence: 92%
“…The compounds of lophatheri also have a great potential to be developed as an agent that inhibits the growth of cancer cells and suppresses the development of viruses that attack the respiratory tract (Chen et al 2019;Kim et al 2016). According to the study conducted by Bahekar and Kale (2016) who obtained that cassava contains high antioxidant compounds and is well used as an anticancer. Jack beans contain flavonoids and phenolic acids which are a rich source of antioxidants (Andriati et al 2018;Sutedja et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The dried ripe fruit of T. chebula is an essential herb used widely in the indigenous system of medicine for its homeostatic, laxative, antitussive, diuretic, and cardiotonic activities [30].…”
Section: Resultsmentioning
confidence: 99%
“…has been used to treat fever, diarrhea, headache, rheumatism conjunctivitis, abscess, demulcent, hypertension, marasmus, irritable bowel syndrome, aches, antiseptic, cyanogenetic, diuretic, dysentery, flu, prostatitis, snake bites, and spasms [34,35]. An in vivo study conducted by Bahekar and Kale [30] also suggested that G. inodorum was a reliable source of plant antioxidant.…”
Section: Resultsmentioning
confidence: 99%